A comparison of four fetal biometry growth charts within an Australian obstetric population. Issue 1 (24th February 2022) - Dry, Candice; Pedretti, Michelle K.; Nathan, Elizabeth; Dickinson, Jan E.
Abstract: Purpose: The aim of this study was to investigate the applicability of four existing fetal growth charts to a local tertiary hospital obstetric population. Method: Four existing fetal growth charts (the Raine study reference charts, INTERGROWTH‐21st charts, World Health Organization (WHO) fetal growth study charts and Australasian Society for Ultrasound in Medicine (ASUM) endorsed Campbell Westerway charts were compared using data from 11651 singleton pregnancy ultrasound scans at King Edward Memorial Hospital (KEMH). The 3rd, 10th, 50th 90th and 97th percentile curves for abdominal circumference (AC) biometry for the KEMH data were calculated and the four primary correlation parameters from fitted 3rd order polynomials (a, b, c and d) were used to generate like‐for‐like comparisons for all charts. Results: The overall comparisons showed a significant variation with different growth charts, giving different percentiles for the same fetal AC measurement. INTERGROWTH‐21st percentile curves tended to fall below those of other charts for AC measurements. Both the Raine Study charts and ASUM charts were the charts of closest overall fit to the local data. Conclusion: Our data show the Raine Study charts are the most appropriate for our population compared with the other three charts assessed suggesting the 'one size fits all' model may not be appropriate. However, additional analysis of biometry measurements, primarily AC, is needed to address the deficiency of data at 14‐18 weeks gestation which exists for the Raine Study data. A reasonable alternative may be to adopt the WHO charts with local calibration (including the 14 ‐ 18 week gestation period).